2021
DOI: 10.1016/j.jbc.2021.100487
|View full text |Cite
|
Sign up to set email alerts
|

Packed red blood cells inhibit T-cell activation via ROS-dependent signaling pathways

Abstract: Numerous observations indicate that red blood cells (RBCs) affect T-cell activation and proliferation. We have studied effects of packed RBCs (PRBCs) on T-cell receptor (TCR) signaling and the molecular mechanisms whereby (P)RBCs modulate T-cell activation. In line with previous reports, PRBCs attenuated the expression of T-cell activation markers CD25 and CD69 upon costimulation via CD3/CD28. In addition, T-cell proliferation and cytokine expression were markedly reduced when T-cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…We have recently reported that erythrocytes interfere with reactive oxygen species (ROS) formation so efficiently that ROS-dependent T-cell activation is blocked by the mere presence of erythrocytes [ 58 ]. This observation clearly implies that the formation of ROS-dependent metabolites in blood may be inhibited as well.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported that erythrocytes interfere with reactive oxygen species (ROS) formation so efficiently that ROS-dependent T-cell activation is blocked by the mere presence of erythrocytes [ 58 ]. This observation clearly implies that the formation of ROS-dependent metabolites in blood may be inhibited as well.…”
Section: Discussionmentioning
confidence: 99%
“…Erythrocytes also interact with other cells of the immune system. Erythrocytes have been shown to inhibit T cell activation or activation-induced apoptosis presumably via reactive oxygen species-dependent pathways [123,124]. Erythrocytes treated with a cancer cell line stimulated T cells to more proliferation and other cytokine secretion profile than if treated with control erythrocytes [125].…”
Section: The Erythrocyte Cytokine and Immune Cell Relationmentioning
confidence: 99%
“…Erythrocyte antioxidant capacity can halter T-cell activation. However, under the oxidant environment of atherothrombosis, erythrocytes are unable to neutralize the ROS related to T-cell activation [ 47 , 48 ]. This incapability of controlling T-cell activation can be provoked by high glucose, homocysteine, and other metabolites.…”
Section: Red Blood Cells In Atherosclerosismentioning
confidence: 99%